PGF2α induces a pro-labour phenotypical switch in human myometrial cells that can be inhibited with PGF2α receptor antagonists - Hamshaw, Isabel; Straube, Anne; Stark, Richard; Baxter, Laura; Alam, Mohammad T.; Wever, Walter J.; Yin, Jun; Yue, Yong; Pinton, Philippe; Sen, Aritro; Ferguson, Gregory D.; Blanks, Andrew M. (Frontiers in Pharmacology, 2023)
Preterm birth is the leading cause of infant morbidity and mortality. There has been interest in developing prostaglandin F2α (PGF2α) antagonists as a new treatment for preterm birth although much of the rationale for their use is based on studies in rodents where PGF2α initiates labour by regressing the corpus luteum and reducing systemic progesterone concentrations. How PGF2α antagonism would act in humans that do not have a fall in systemic progesterone remains unclear. One possibility, in addition to an acute stimulation of contractions, is a direct alteration of the myometrial smooth muscle cell state towards a pro-labour phenotype. In this study we developed an immortalised myometrial cell line, MYLA, derived from myometrial tissue obtained from a pregnant, non-labouring patient as well as a novel class of PGF2α receptor (FP) antagonist. We verified the functionality of the cell line by stimulation with PGF2α, which resulted in Gq specific coupling and Ca2+ release that were inhibited by FP antagonism. Compared to four published FP receptor antagonists, the novel FP antagonist N582707 was the most potent compound (Fmax 7.67 ± 0.63 (IC50 21.26 nM), AUC 7.30 ± 0.32 (IC50 50.43 nM) and frequency of Ca2+ oscillations 7.66 ± 0.41 (IC50 22.15 nM)). RNA-sequencing of the MYLA cell line at 1, 3, 6, 12, 24 & 48 hours post PGF2α treatment revealed a transforming phenotype from a fibroblastic to smooth muscle mRNA profile. PGF2α treatment increased expression of MYLK, CALD1 and CNN1 as well as the pro-labour genes OXTR, IL6 and IL11 which were inhibited by FP antagonism. Concomitant with inhibition of a smooth muscle, pro-labour transition, FP antagonism increased the expression of the fibroblast marker genes DCN, FBLN1 and PDGFRA. Our findings suggest that in addition to the well described acute contractile effect, PGF2α transforms myometrial smooth muscle cells from a myofibroblast to smooth muscle, pro-labour like state, and that the novel compound N582707 has potential for prophylactic use in preterm labour management beyond its use as an acute tocolytic drug.